A Corral in a Chinese Coral Lake? Territorial Sovereignty, Maritime Interests, Power Allocation As Defined by China’s Supreme People’s Court, and Its Impact on Foreign Private Sector Management Across and Beyond the East and South China Seas - Jones, David A. (Advances in Social Sciences Research Journal, 2017)
In response to the decision of the United Nations Tribunal Decision in The Philippines vs. China, announced on 12 July 2016, three weeks later on 02 August 2016 China’s Supreme People’s Court declared “judicial power is an important component of national sovereignty. People’s courts will actively exercise jurisdiction over China’s territorial waters, support administrative departments to legally perform maritime management duties, equally protect the legal rights of Chinese and foreign parties involved and safeguard Chinese territorial sovereignty and maritime interests.”1 Does this reflect an advancing China portraying itself as a peace keeper, or a regressing China, determined to minimize international laws and customs as well as the laws of foreign nations in favour of its own parochial interpretations? Countries including the United States assert jurisdiction over their own nationals and companies they have chartered, abroad as at home, in the Foreign Corrupt Practices Act (FCPA), amongst other laws, generally with domestic and international judicial approval. With its recent declaration, China’s highest court appears to have gone well beyond this convention, vowing to exercise Chinese jurisdiction over land and waters beyond its homeland to “safeguard Chinese territorial sovereignty and maritime interests.” This paper will reflect on that holding that seemingly goes against both letter and spirit of the United Nations Tribunal determination, and almost certainly conflicts with the domestic laws of a great many other sovereign states that border the East and South China Seas, potentially fan out globally across Eurasia, the Indian Ocean, and the Mediterranean Sea, wherever China’s “One Belt, One Road” (OBOR) goes. What then will be expected of shipping companies, insurance carriers, purchasers and sellers of goods transported over the high seas, particularly in destination contracts? Should Chinese laws prevail? If China openly defies the holding of a United Nations court, should it continue to hold its United Nations Security Council permanent seat?